2017
DOI: 10.1136/jech-2017-209691
|View full text |Cite
|
Sign up to set email alerts
|

Association between psychosocial work conditions and latent alcohol consumption trajectories among men and women over a 16-year period in a national Canadian sample

Abstract: Our study suggests that workplace physical exertion and psychological demands may be associated with different alcohol consumption trajectories among men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…This pattern of opposite effects was recently also highlighted in a study that computed genetic correlations and reported high alcohol use frequency to be genetically correlated with higher socio-economic status and lower risk of psychiatric disorders, whereas high alcohol consumption quantity was genetically correlated with lower socio-economic status and higher psychiatric disorder risk (Marees et al, 2019 ). Similar to smoking, it could be that excessive alcohol use is a way to cope with job stress (Dobson, Ibrahim, Gilbert-Ouimet, Mustard, & Smith, 2018b ). There was also consistent evidence that mental disorders increase (problematic) alcohol use, without strong effects in the other direction.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of opposite effects was recently also highlighted in a study that computed genetic correlations and reported high alcohol use frequency to be genetically correlated with higher socio-economic status and lower risk of psychiatric disorders, whereas high alcohol consumption quantity was genetically correlated with lower socio-economic status and higher psychiatric disorder risk (Marees et al, 2019 ). Similar to smoking, it could be that excessive alcohol use is a way to cope with job stress (Dobson, Ibrahim, Gilbert-Ouimet, Mustard, & Smith, 2018b ). There was also consistent evidence that mental disorders increase (problematic) alcohol use, without strong effects in the other direction.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 It has been argued that jobs with high demands, including high-strain jobs, may be related to alcohol use through the pathway of tension release and self-medication. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 Other studies found notable differences between men and women or specifically only found associations among men. 9 , 17 These studies varied in their study populations, study design and measures.…”
Section: Introductionmentioning
confidence: 99%
“…Flood and Moen (2015) found that employment was largely associated with less time spent in meal preparation among men and women ages 55 to 74. Stressful working conditions are also linked to higher drinking (Dobson et al, 2018). However, in a qualitative study, some respondents described work relationships as having positive spillovers onto food choices, such as increasing efforts to eat healthy food around colleagues or sharing meal ideas (Devine et al, 2003).…”
Section: Introductionmentioning
confidence: 99%